Methodology of integral evaluation of enterprise financial potential in the information society - Khrushch, Nila; Grygoruk, Pavlo (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
Companies in the Ukraine are presently researching optimal forms of capital and current expense provision in an effort towards resolving their financial problems through quantitative evaluation of enterprises’ real financial ability. Bearing in mind the multidimensional nature of financial potential i.e. large numbers of diverse indexes, it is often impossible to precisely determine its causes and effects and choose the appropriate index from the aggregate. In such cases indexes ought to be correlated to form a system. The study of this system by means of one-dimensional statistical method does not offer the possibility of considering all diversities and complications in the correlation of indexes. It is possible to solve the above mentioned problem by means of data aggregation which aims at creating a compact and visible database, that is suitable for further research, making decisions and drawing conclusions. The concept proposed herein is an composite index system for the construction and interpretation of obtained results. The main hypothesis is its usefulness in describing the phenomenon and in obtaining the similar conclusions as those obtained from the whole aggregate of available indicators.

Przedsiębiorstwa na Ukrainie poszukują obecnie optymalnych form kapitału oraz realizacji bieżących płatności i w celu rozwiązywania problemów finansowych wykorzystują ilościową ocenę rzeczywistej zdolności finansowej. Wielowymiarowy charakter potencjału finansowego i bardzo liczny zbiór wskaźników go opisujących powodują, że często nie jest możliwe wybranie tylko jednego właściwego wskaźnika. W takich przypadkach konieczne jest wykorzystanie grupy wskaźników, które są ze sobą powiązane i tworzą pewien układ. Natomiast badanie tego potencjału za pomocą jednowymiarowej metody statystycznej nie pozwala na uwzględnienie wszystkich różnic i powiązań występujących między wskaźnikami. Możliwe jest rozwiązanie powyższego problemu poprzez agregację wskaźników i utworzenie indeksu złożonego, który będzie wykorzystywany w dalszych badaniach oraz do oceny uzyskanych wyników, podejmowania decyzji i wyciągania wniosków. W niniejszej pracy przedstawiono propozycję metody wyznaczania indeksu złożonego, który pozwala na obiektywną ocenę wyników działalności przedsiębiorstwa i może być wykorzystany do racjonalnego wyboru strategicznych kierunków jego rozwoju.